2003
DOI: 10.1046/j.1365-2745.2003.00745.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variations in mortality of the biennial plant, Lysimachia rubida: effects of intraspecific competition and environmental heterogeneity

Abstract: Summary 1We studied mortality, growth and spatial distribution of individuals of Lysimachia rubida to elucidate causes and consequences of temporal and spatial variations in mortality. This short-lived monocarpic biennial grows in open dry habitats on rocky coastal cliffs of the subtropical Bonin (Ogasawara) Islands, Japan. 2 All individuals of two successive cohorts that appeared in a 8 × 8-m quadrat were mapped, and their fate and size were recorded at 2-3 month intervals from March 1998 to July 2000. We ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 56 publications
0
50
0
2
Order By: Relevance
“…In the present study, the birth rates recorded for the four populations during the rainy season, followed the pattern found for several vegetation types in Brazil and in the world. Water shortage is the main factor responsible for the mortality of herbaceous plants in dry (Mondragón et al, 2004;Volis et al, 2004;Nippert et al, 2006;Silva et al, 2008) and humid (Zotz, 1998;Castellani et al, 2001;Nordbakken et al, 2004;Vilà, Bartolomeus, Gimeno, Traveset, & Moragues, 2006) forest areas during dry seasons; however, herbivory (Maron, & Crone, 2006;Gotelli, 2007), intraspecific competition (Suzuki, Kudoh, & Kachi, 2003;Volis et al, 2004) and interspecific competition (Miller & Duncan, 2003;Nordbakken et al, 2004;Thomson, 2005) have been identified as the main causes of mortality during the rainy season.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the birth rates recorded for the four populations during the rainy season, followed the pattern found for several vegetation types in Brazil and in the world. Water shortage is the main factor responsible for the mortality of herbaceous plants in dry (Mondragón et al, 2004;Volis et al, 2004;Nippert et al, 2006;Silva et al, 2008) and humid (Zotz, 1998;Castellani et al, 2001;Nordbakken et al, 2004;Vilà, Bartolomeus, Gimeno, Traveset, & Moragues, 2006) forest areas during dry seasons; however, herbivory (Maron, & Crone, 2006;Gotelli, 2007), intraspecific competition (Suzuki, Kudoh, & Kachi, 2003;Volis et al, 2004) and interspecific competition (Miller & Duncan, 2003;Nordbakken et al, 2004;Thomson, 2005) have been identified as the main causes of mortality during the rainy season.…”
Section: Discussionmentioning
confidence: 99%
“…For example, individuals established in the "between canopies" microhabitat lose faster water to the environment, suffering water deficit more quickly and more intensely (characteristic of the caatinga), being unable to keep themselves alive in these microhabitats. In addition to water stress, other environmental factors can cause mortality of individuals in both microhabitats, such as the impact of rain on newly germinated seedlings or frail individuals who survived the previous drought ; intra and interspecific competition for resources (Nordbakken, Rydgren, & Okland, 2004;Suzuki, Kudoh, & Kachi, 2004;Vilá, Bartolomeus, Gimeno, Traveset, & Moragues, 2006); attack by pathogens (Araújo, & Ferraz, 2003;Silveira, Araújo, Araújo, & Willadino, 2005); and herbivory (Belsky, 1990;Hanley, 1998;Leimu, & Lehtila, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the population dynamics of herbaceous species in dry (Miller and Duncan, 2003;Santos et al, 2013b;Vega and Montaña, 2004;Volis et al, 2004;Wang, 2005) and wet forests (Baeten et al, 2009;Flores-Torres and Montaña, 2012;Kolb et al, 2007;Pino et al, 2007;Suzuki et al, 2003;) around the world have shown that heterogeneity in establishment conditions (microhabitats) for seedlings may limit population sizes and occurrence. This phenomenon was observed for some herbaceous populations in the dry forest (Caatinga) of Brazil (Andrade et al, 2007;Araújo et al, 2005;Lima et al, 2007;Reis et al, 2006;Santos et al, 2012;Silva et al, 2008), and it was also observed in this study.…”
Section: Microhabitats Vs Densitymentioning
confidence: 99%
“…García- Cháves et al, 2014;Vega and Montaña, 2004;Wang, 2005). In rocky outcrops that occur within forested areas, the occurrence of a moss layer and sediment accumulation in rocky outcrop crevices are sufficient to provide a substrate and promote the development of a dense layer of herbaceous plants during the growing season, when temperature and humidity conditions are favorable for seedling recruitment, establishment and survival (Araújo et al, 2005;Nordbakken et al, 2004;Silva et al, 2008;Suzuki et al, 2003). Water accumulation in rocky outcrop crevices may explain the high density of individuals of the four species in the rocky microhabitat, especially C. obliqua, which has a preference for this microhabitat.…”
Section: Microhabitats Vs Densitymentioning
confidence: 99%